Effect of sevoflurane pretreatment in relieving liver ischemia/reperfusion-induced pulmonary and hepatic injury - Xu,Guiping (2019)
Abstract Purpose To investigate the effect of sevoflurane preconditioning on ischemia/reperfusion (I/R)-induced pulmonary/hepatic injury Methods Fifty-one Wistar rats were randomly grouped into sham, I/R, and sevoflurane groups. After reperfusion, the structural change of the lung was measured by Smith score, the wet and dry weights (W/D) were determined, malondialdehyde (MDA) myeloperoxidase (MPO) content was determined colorimetrically and by fluorescence, respectively, and matrix metalloprotein-9 (MMP-9) mRNA was quantified by RT-PCR. Biopsy and morphological analyses were performed on liver tissue, activities of aspartate aminotransferase (AST) and alanine aminotransferase (ALT) were determined, and tumor necrosis factor-alpha (TNF-α) level was determined. Results The sham group showed no changes in tissue structure. Structural lesions in the sevoflurane and I/R groups were mild and severe, respectively. Smith score, W/D, MDA, MPO, and MMP mRNA showed the same trend, and were increased in the I/R group and recovered in the sevoflurane group, compared with the sham group (both P<0.05). AST and ALT were significantly increased compared to the sham group (AST: 655±52.06 vs . 29±9.30 U/L; ALT: 693±75.56 vs . 37±6.71 U/L; P<0.05). In the sevoflurane group, AST and ALT levels were significantly decreased (464±47.71 and 516±78.84 U/L; P<0.001). TNF-α presented similar results. Conclusion The protection of lung and liver by sevoflurane may be mediated by inhibited leukocyte recruitment and MMP-9 secretion.